THE FINANCIAL FEASIBILITY OF RICE DRYERS: A Case Study in Subang District, West Java - Dewa Ketut Sadra Swastika (Indonesian Agency for Agricultural Research and Development, 2012)
Drying is a critical activity in rice postharvest handling. Any delay in drying will result in quality and quantity losses. Farmers and traders prefer to sell wet grain rather than dried grain of unhulled rice due to less attractive incentive for them to do drying. The study was conducted in Subang District, West Java, during March-June 2011 using survey method to analyze the financial feasibility of rice dryers. The respondents interviewed were 15 rice millers who have either sun-drying floor or mechanical dryer, or both. The main collected data were the investment cost, operational cost, maintenance cost, and the revenue of the dryers. The data were analyzed by using shortterm and long-term financial analyses to assess the profitability and feasibility of some drying technologies. The results showed that there were at least three drying technologies in the study area, namely sun-drying floor, flatbed dryer using gas fuel (gas dryer), and flatbed dryer using rice husk fuel (husk dryer). Under the mean capacity, the short-run MBCR of technological change from sun dryer to gas dryer was 1.29, while from sun dryer to husk dryer was 1.45. The long-run analysis showed that the IRRs were 44.44% for sun dryer, 233.47% for gas dryer, and 260.49% for husk dryer. These results showed that among the three drying technologies, husk dryer is the most profitable, most feasible, and most prospective to be adopted. Therefore, this type of dryer should be intensively promoted to the farmers’ group associations, rice traders, and rice millers. The government support in terms of rice dryers for farmers’ group associations should be focused on husk dryer.